British Borneo sketches of Brunai, Sarawak, Labuan, and North Borneo - Treacher, W. H. (Silverfish Malaysian classics, 2020)
In 1670, Charles II granted to the Hudson's Bay Company a Charter of Incorporation, His Majesty delegating to the Company actual sovereignty over a very large portion of British North America, and assigning to them the exclusive monopoly of trade and mining in the territory. Writing in 1869, Mr. William Forsyth, Q.C., says: - "I have endeavoured to give an account of the constitution and history of the last of the great proprietary companies of England, to whom a kind of delegated authority was granted by the Crown. It was by some of these that distant Colonies were founded, and one, the most powerful of them all, established our Empire in the East and held the sceptre of the Great Mogul. But they have passed away and the Hudson's Bay Company will be no exception to the rule. It may continue to exist as a Trading Company, but as a Territorial Power it must make up its mind to fold its (buffalo) robes round it and die with dignity." Prophesying is hazardous work. In November, 1881, two hundred and eleven years after the Hudson's Bay Charter, and twelve years after the date of Mr. Forsyth's article, Queen Victoria granted a Charter of Incorporation to the British North Borneo Company.